DEVELOPING “ANTI-CYBERBULLYING INTELLIGENCE” INSIDE SOCIAL MEDIA USING JOHARI WINDOW-KEN WATANABE-PROBLEM SOLVING 101 METHODS - Gamayanto, Indra; wibowo, Sasono; Setiadi, De Rosal Ignatius Moses (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2020)
Abstract: Cyberbullying is a complex problem because it produces a large impact on the individuals who experience it. Furthermore, cyberbullying is a problem that may not have found the right solution in this day and sometimes, there is no problem-solving. Furthermore, this research is a development from three research: The Development and Implementation of Wise Netizens (E-Comments) in Indonesia and journals; the journal Developing